Profil Peresepan Penggunaan Obat Antihipertensi di Puskesmas Pare Temanggung Periode Maret - April 2021 - S Sumariyanti; Rina Widiastuti; Rini Sulistyowati; Andita Eltivitasari (Indonesian Journal on Medical Science, 2023)
Hypertension is a degenerative disease that has a high incidence rate. Therapy given to hypertensive patients is usually carried out for a long time. The general goal of hypertension treatment is to reduce mortality and morbidity associated with target organ damage such as heart failure, coronary heart disease or chronic kidney disease. This study aims to provide an overview of the prescribing profile of antihypertensive drugs at the Pare Temanggung Health Center in March-April 2021 which includes drug class, drug type, drug combination, drug dose, frequency of drug administration, and duration of drug administration. This type of research is descriptive with a retrospective approach. The study used the total sampling method and obtained 100 prescription data for hypertension patients. The collected data will be processed and analyzed and then presented in tabular form. The results showed that most hypertension patients were aged 51-75 (66%). Female patients (63%) were more than male patients (37%). The most common use of antihypertensive drugs is as a single therapy (84%). The most commonly used hypertension drug class was Calcium Channel Blocker/CCB (89%). The most commonly used type of hypertension drug was amlodipine (88%). The duration of hypertension drug therapy was mostly around 10 days (88%).